1991
DOI: 10.1002/ijc.2910490621
|View full text |Cite
|
Sign up to set email alerts
|

Integrin expression in human melanoma cell lines: Heterogeneity of vitronectin receptor composition and function

Abstract: Ten human melanoma cell lines were examined for integrin-receptor expression using a panel of antibodies directed against different integrin subunits. Considerable heterogeneity was detected for levels of expression of 7 integrins, including the alpha v beta 3 vitronectin receptor where a correlation between tumorigenic capacity in athymic nude mice and alpha v beta 3 levels was found. Detailed analysis of the vitronectin receptor on these lines revealed heterogeneity of composition. In one cell line, VUP, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…Immunoprecipitation with antibody to av (13C2) coprecipitated a (1-sized band from both OM431 and V(+)B2 but not from the SP6.5 or OCM-I cell lines. It appears that OM431 is the second uveal melanoma cell line that we have shown to lack avP3 but to express avil (Marshall et al, 1991). Figure 1 also confirms the flow cytometry data ( Table 2) that avP5 is expressed weakly by OM431, SP6.5, OCM-I and, as reported previously, V + B2 (Marshall, 1995).…”
Section: Immunoprecipitationsupporting
confidence: 89%
See 3 more Smart Citations
“…Immunoprecipitation with antibody to av (13C2) coprecipitated a (1-sized band from both OM431 and V(+)B2 but not from the SP6.5 or OCM-I cell lines. It appears that OM431 is the second uveal melanoma cell line that we have shown to lack avP3 but to express avil (Marshall et al, 1991). Figure 1 also confirms the flow cytometry data ( Table 2) that avP5 is expressed weakly by OM431, SP6.5, OCM-I and, as reported previously, V + B2 (Marshall, 1995).…”
Section: Immunoprecipitationsupporting
confidence: 89%
“…In contrast the av,B1-positive lines were either poorly or non-tumorigenic. In addition, using flow cytometry we have measured expression of av,5, avP6 and avP8 on the nine cutaneous melanoma cell lines already examined for av,B3 expression (Marshall et al, 1991). Together with the data reported here, we have found that formation of subcutaneous xenografts by 17 human (cutaneous and uveal) melanoma lines correlates with an avP3-positive, av,B1-negative phenotype.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A correlation has been reported between increased expression of avb3 and aIIbb3 integrins and increased invasive and metastatic potential of melanoma cells. 13,14 Modulation of a5 integrin has been shown to be involved in tumor progression and metastasis, but its role is still not very clear. High levels of a5 expressions was shown to be negatively correlated with the progression of many carcinomas including breast carcinoma and melanoma.…”
Section: Introductionmentioning
confidence: 99%